2019
DOI: 10.21521/mw.6246
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of adropin in the small intestine of rats

Abstract: The aim of this study was to determine the occurrence and distribution of adropin in the small intestine in control and gastrectomized rats. The study was carried out on 12 Wistar rats. Six control rats (SHO) underwent a sham operation. Six rats were subjected to gastrectomy (Gx); i.e. resection of the antrum and the glandular part of the stomach. Six weeks after the surgery, the rats were sacrificed. The duodenum and middle part of the jejunum were collected for immunohistochemical and immunofluorescence proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Kumar et al [ 1 ] showed that serum adropin levels were elevated proportionally to the increase in dietary fat intake and suppressed by fasting. Moreover, the immunopositive reaction for ADR in the duodenum, jejunum, crypts, and enterocytes located along the entire length of the villi suggests its role in the functioning of the GI tract [ 5 ]. In the pancreas, ADR was detected in acinar cells [ 3 ] and in the capillaries of the islets of Langerhans [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kumar et al [ 1 ] showed that serum adropin levels were elevated proportionally to the increase in dietary fat intake and suppressed by fasting. Moreover, the immunopositive reaction for ADR in the duodenum, jejunum, crypts, and enterocytes located along the entire length of the villi suggests its role in the functioning of the GI tract [ 5 ]. In the pancreas, ADR was detected in acinar cells [ 3 ] and in the capillaries of the islets of Langerhans [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…ADR34-76, which is derived from its 76-amino acid precursor, has biological activity. Over several years, the presence of adropin in blood and various organs, including the brain, kidneys, heart, blood vessels, pancreas, and small intestine, has been demonstrated [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation